ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH SEBELUM DAN SESUDAH PROGRAM BPD REGIONAL CHAMPION DENGAN METODE RGEC (Studi Kasus PT. Bank Pembangunan Daerah Jawa Timur Tbk Periode 2007-2014) - LUCKY LARAS KINANTI (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study is to compare financial performance of Regional Development Bank in East Java who called Bank Jatim before and after BPD Regional Champion in 2007-2014. This study is analyzed by using RGEC approach and then BRC provision. The type of of research being used is descriptive research type. Variables and measurement in this research consist of Risk Profile, GCG, Earnings, and Capital Factor. The result show that there aren’t any difference of financial performance before and after BPD Regional Champion. Risk profile factor measured by NPL and LDR. In NPL ratio, the result show that before BRC is better than after BRC because there are increasing number of NPL ratio. Otherwise on LDR, by using LDR RGEC method there is a decreasing level but by using BRC criteria Bank Jatim has succesfull to apply BRC criteria because LDR criteria in BRC is between 78 - 100%. GCG Bank Jatim has good or healty category from 2009-2014 because the composite value is between 1,5 – 2,5. Earning factor assessment is measured by using ROA and NIM ratio. The number of ROA ratio is in very good level and success to fulfill BRC criteria because ROA the number of ROA  ratio always above 2,5%. In NIM ratio, Bank Jatim has very good level but cannot fulfill BRC criteria because the  NIM  ratio  is  always above  5,5  while  criteria the  BRC criteria is  maximum 5,5%.  Using CAR indicator, Bank Jatim has very good capital and success to fulfill BRC criteria that minimum 15%.Keywords : Financial performance, Risk Profile, Good Corporate Governance, Earnings, Capital, RGEC